3D cut image modification - MORENO DANIEL; SAMUEL EDWARD HARE; MAXIMOV LAZAROV MAKSIM; MATHEW TONY; MCPHEE ANDREW JAMES; SHANG WENTAO; GOODRICH KYLE (2022)
Aspects of the present disclosure relate to a system including a computer-readable storage medium storing at least one program and a method for performing operations including: receiving, by a messaging application, an image generated by a camera of a user; displaying an option for clipping an object depicted in the image; determining whether an object is depicted in the image; selectively enabling selection of an option for clipping the object based on determining whether the object is depicted in the image; when the option is enabled, receiving an input selecting an option for clipping an object depicted in the image; in response to receiving the input, segmenting the image to separate the object from other portions depicted in the image; extracting an object from the image; and adding the extracted object as a virtual object to the new image. 本公开内容的各方面涉及一种系统，该系统包括存储至少一个程序的计算机可读存储介质和用于执行操作的方法，所述操作包括：由消息收发应用接收由用户的摄像装置生成的图像；显示用于裁剪图像中描绘的对象的选项；确定图像中是否描绘了对象；基于确定图像中是否描绘了对象，选择性地启用对用于裁剪对象的选项的选择；当启用该选项时，接收选择用于裁剪图像中描